2012
DOI: 10.3390/md10061203
|View full text |Cite|
|
Sign up to set email alerts
|

Simplexins P–S, Eunicellin-Based Diterpenes from the Soft Coral Klyxum simplex

Abstract: Four new eunicellin-based diterpenes, simplexins P–S (1–4), and the known compound simplexin A (5), have been isolated from the soft coral Klyxum simplex. The structures of the new metabolites were determined on the basis of extensive spectroscopic analysis, particularly 1D and 2D NMR experiments. Compounds 1 and 3–5 were shown to exhibit cytotoxicity against a limited panel of cancer cell lines, 3 being the most cytotoxic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…[15] Eunicellin 20 showed activity against the proliferation of K-562, CCRF-CEM, T-47D, and MOLT-4 tumor cells, with ED 50 values of 15.9, 5.9, 29.7, and 8.4 μM, respectively. [16]…”
Section: Klyxum Simplex (Family Alcyoniidae)mentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Eunicellin 20 showed activity against the proliferation of K-562, CCRF-CEM, T-47D, and MOLT-4 tumor cells, with ED 50 values of 15.9, 5.9, 29.7, and 8.4 μM, respectively. [16]…”
Section: Klyxum Simplex (Family Alcyoniidae)mentioning
confidence: 99%
“…Three hydroperoxyeunicellins, klysimplexins D (18) and M (19), along with simplexin R (20) (Figure 10), were isolated from K. simplex. [14][15][16] The structures of eunicellins 18-20 were determined by spectroscopic methods. At a concentration of 10 μM, eunicellin 19 was found to significantly reduce the expression of inducible nitrogen oxide synthase (iNOS).…”
Section: Klyxum Simplex (Family Alcyoniidae)mentioning
confidence: 99%
“…Previous studies showed that many eunicellin-based diterpenes discovered from soft corals exhibited cytotoxic and anti-inflammatory activities [1,2,3,4,5,6,7,8,9,10,11,12,13,14]. The soft coral Cladiella krempfi has been found to generate several types of metabolites including eunicellin-type diterpenoids [15] and pregnane-type steroids [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies about the discovery of versatile structures and bioactivities of eunicellin-type compounds isolated from soft corals have been reported [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15]. The soft coral Cladiella krempfi has been found to generate several types of metabolites including eunicellin-type diterpenoids [16,17] and pregnane-type steroids [18,19,20].…”
Section: Introductionmentioning
confidence: 99%